Land-ice elevation changes from photon-counting swath altimetry: first applications over the Antarctic ice sheet - Young,DA; Lindzey,LE; Blankenship,DD; Greenbaum,JS; Garcia,De Gorordo A; Kempf,SD; Roberts,JL; Warner,RC; Van,Ommen T; Siegert,MJ; Le,Meur E (Journal of Glaciology, 2015)
Satellite altimetric time series allow high-precision monitoring of ice-sheet mass balance.Understanding elevation changes in these regions is important because outlet glaciers along ice-sheetmargins are critical in controlling flow of inland ice. Here we discuss a new airborne altimetry datasetcollected as part of the ICECAP (International Collaborative Exploration of the Cryosphere by AirborneProfiling) project over East Antarctica. Using the ALAMO (Airborne Laser Altimeter with MappingOptics) system of a scanning photon-counting lidar combined with a laser altimeter, we extend the2003–09 surface elevation record of NASA’s ICESat satellite, by determining cross-track slope and thusindependently correcting for ICESat’s cross-track pointing errors. In areas of high slope, cross-trackerrors result in measured elevation change that combines surface slope and the actual z=t signal.Slope corrections are particularly important in coastal ice streams, which often exhibit both rapidlychanging elevations and high surface slopes. As a test case (assuming that surface slopes do not changesignificantly) we observe a lack of ice dynamic change at Cook Ice Shelf, while significant thinningoccurred at Totten and Denman Glaciers during 2003–09.